Persepsi Masyarakat Terhadap Keberadaan Peternakan Babi di Desa Jono Oge Kecamatan Sigi Biromaru Kabupaten Sigi - Haerani Maksum; Ritha Rahayu; Suharno H. Syukur; Taufiq Eka Riandhana (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This research was conducted in dusun 04 Jono Oge Village, Sigi Biromaru Subdistrict, Sigi Regency, has been conducted from October 26 to November 10, 2020. The type of research used is qualitative descriptive. The method used is survey method (observation and interview). The population in this study is the entire community in the village of 04 Jono Oge village which amounts to 758 people. Determination of the number of samples using descriptive statistics based on slovin formula as many as 42 people and the method of taking respondents using purposive sampling. The data analysis used in this study is Descriptive Statistics using the Likert scale. The results of this study are known that the public perception of the existence of pig farms in the village of Jono Oge Sigi Biromaru Subdistrict Sigi regency with a score of 1488 is in the category of quite disturbed. This means that respondents feel quite disturbed by the existence of pig farms because the pig farm stands close to the settlement, when it is known that setting up a pig farm should be far from the settlement, so as not to disturb the comfort of the people living in Dusun 04 Jono Oge Village.